Penerapan Model Eksponensial dan Model Logistik untuk Memproyeksikan Jumlah Penduduk Kabupaten Lombok Timur - Khairunnisa, Jihan (Program Studi Matematika, Universitas Nusa Cendana, 2025)
The significant population growth in East Lombok Regency presents challenges in policy planning, particularly in the education sector. To anticipate its impact, this research aims to compare exponential and logistic models in projecting the population until 2033. Employing a quantitative approach and utilizing secondary data from the Central Bureau of Statistics, this study analyzes population estimates using both models. The research findings indicate that the exponential model provides population estimates with higher confidence than the logistic model. This research can serve as a foundation for the East Lombok Regency Government in making decisions regarding development and human resource enhancement to improve community welfare. Additionally, the research findings demonstrate that mathematical models, such as population growth models, can be adapted for real-world context in differential equation courses, enriching mathematics learning.